Influence of climate drivers and fishing effort on fish stock condition using dynamic factor analysis: a case study from the Caspian Sea - Hasan Fazli; Gholam Reza Daryanabard; Akbar Pourgholami; Seyed Abbas Hoseini; Mohammad Reza Mirzaei; Parto Bahreini (Scientia Marina)
We explored the potential impact of climate-driven factors [East Atlantic-West Russian pattern, sea surface level (SSL), sea surface temperature (SST) and river discharge] alongside fishing effort (E) on shifts in aquatic species demographics. Dynamic factor analysis (DFA) was employed for indices of annual catch (Cat), Abundance (Abu), fingerlings released, spawning stock biomass (SSB), percentage of immature (Imm), mega spawners and relative condition factor from datasets of Chelon aurata and Rutilus kutum over 30 years. Of 324 DFA models, the optimal model for both species included a “diagonal and unequal“ R matrix with SST, SSL and E as exploratory covariates, revealing one common trend for C. aurata and SST and SSL and two common trends for R. kutum. Within the common trend for C. aurata, Abu and SSB displayed a strong positive correlation with trend 1. In the case of R. kutum, the first common trend showed a positive correlation with Cat, Abu, and SSB and a negative one with Imm. Also, rising SST and decreasing SSL negatively affect species’ health. This study emphasizes integrated monitoring and management to sustain fish species and the ecosystem, advocating adaptive strategies to counter environmental stressors and anthropogenic effects.